Intrinsic stress formation in multi-component coatings produced by plasma ion deposition in modes of DC and pulse bias potentials - Kalinichenko, A.I.; Kozionov, S.A.; Strelnitskij, V.E. (Вопросы атомной науки и техники, 2016)
In the model of nonlocal thermoelastic peak of low-energy ion a formula for intrinsic stress in multi-component material deposited from mixed beam of differently charged ions in modes of DC and pulse bias potentials is derived. Calculation of intrinsic stress σ depending on bias potential U in coating Cr-Al-N deposited from mixed ion beam Cr(50%)Al(50%) is executed at different modes and substrate temperatures T₀. It is shown that maximum of σ(U) in pulse bias potential mode shifts towards higher U as compared with DC mode whereas increase of T₀ leads to opposite effect. У рамках моделі нелокального термопружного піка низькоенергетичного іона отримана формула для внутрішніх напружень у багатокомпонентному матеріалі, що осаджується зі змішаного пучка різнозаряджених іонів у режимах постійного й імпульсного потенціалів. Проведено розрахунок залежності внутрішніх напружень σ від потенціалу зміщення U у покритті Cr-Al-N, що осаджується зі змішаного потоку Cr(50%)Al(50%) іонів при різних режимах і температурах осадження T₀. Показано. що в режимі імпульсного потенціалу максимум кривої σ(U) зміщується у бік більших значень U, у порівнянні з режимом постійного потенціалу. Підвищення T₀ веде до зворотного ефекту. В рамках модели нелокального термоупругого пика низкоэнергетического иона получена формула для внутренних напряжений в многокомпонентном материале, осаждаемом из смешанного пучка разнозаряженных ионов в режимах постоянного и импульсного потенциалов. Проведен расчет зависимости внутренних напряжений σ от потенциала смещения U в покрытии Cr-Al-N, осаждаемом из смешанного потока Cr(50%)Al(50%) ионов при различных режимах и температурах осаждения T₀. Показано, что в режиме импульсного потенциала максимум кривой σ(U) смещается в сторону больших значений U, по сравнению с режимом постоянного потенциала. Повышение T₀ ведет к обратному эффекту.